Kontribusi determinan pad sebelum dan selama covid-19 pada pemerintahan kabupaten/kota di Provinsi Sumatera Selatan - Nurhayati, Siti; Sari, Kartika Rachma; Aryani, Yuli Antina (Co-Creation : Jurnal Ilmiah Ekonomi Manajemen Akuntansi dan Bisnis, 2023)
The purpose of this study is to analyze whether there is a difference between the results of the Regency/City contribution ratio before and during Covid-19 to the local revenue of the Regency/City government in South Sumatra Province. With research method quantitative method by utilizing the Regency/City government budget realization reports in South Sumatra in 2018-2021. The tests carried out are contribution analysis, normality test, homogeneity test, and Mann Whitney test on data taken through purposive sampling technique. Data processing was carried out with the help of SPSS version 26 software. The results is there are no significant differences between local taxes, regional levies, legitimate regional wealth management results, Other Lawful Local Revenue. There are no significant differences between before and during Covid-19. It can be concluded that there is no difference between PAD before and during Covid-19.